Diseño paramétrico aplicado al desarrollo de mobiliario a partir de materias primas residuales - Curipallo Peralvo, Alexis Israel (2023)
The current project aims to harness the potential of residual raw materials in the design and development of furniture. These materials, which would otherwise be considered waste, become valuable resources through the application of parametric design and the use of digital manufacturing tools, serving as the foundation for furniture conception. Parametric design allows us to create efficient and personalized models and prototypes by adapting shapes, sizes, and features based on predefined parameters. We can optimize the use of these materials by maximizing their utilization and minimizing waste. The use of digital manufacturing tools, such as CNC cutting machines, provides us with the possibility to materialize and produce designs precisely and efficiently. These technologies enable us to work with a wide variety of materials, including those sourced from waste or recycled materials. By utilizing residual raw materials, we promote sustainability and the circular economy. By reducing our reliance on new raw materials, we avoid generating additional waste and contribute to minimizing environmental impact.